Thermochemistry and Equilibration Time Scales for a Rechargeable Lithium Ion Battery. (10th December 2015) - Cain, Stephen R.; Infantolino, William; Anderson, Allen; Tasillo, Edward; Wolfgramm, Paul
Abstract: The open terminal voltage of a lithium ion battery is measured at temperatures ranging from 0 °C to 50 °C in increments of 10 °C. Primary focus is on three states of charge of the battery (full charge, late life, charge depletion). Estimates of the enthalpy, ΔH, and the entropy, ΔS, of the battery reaction are made using the established thermochemical relationship between the open terminal voltage and the Gibbs free energy, ΔG. As expected, ΔS is found to be dependent on the state of charge. The enthalpy also shows some dependence on the state of charge, which is at variance with the ideal Nernstian behavior. This may attributed to non-equivalence of intercalation sites as well as near neighbor interactions. Furthermore, the rate of discharge has little apparent effect on these results. An equilibration time well in excess of 20 hours is also observed.